Noncoding RNAs in disease - Lekka, Evangelia; Hall, Jonathan (FEBS letters, 2018)
Noncoding RNAs are emerging as potent and multifunctional regulators in all biological processes. In parallel, a rapidly growing number of studies has unravelled associations between aberrant noncoding RNA expression and human diseases. These associations have been extensively reviewed, often with the focus on a particular microRNA (miRNA) (family) or a selected disease/pathology. In this Mini‐Review, we highlight a selection of studies in order to demonstrate the wide‐scale involvement of miRNAs and long noncoding RNAs in the pathophysiology of three types of diseases: cancer, cardiovascular and neurological disorders. This research is opening new avenues to novel therapeutic approaches.